GUIDELINES ON THE RIGHTS AND OBLIGATIONS OF HUSBANDS AND WIVES IN THE HOME AND THEIR RELEVANCE TO CHARACTER AND MORAL EDUCATION (UQUDUL LUJAIN) - Moch Faisal; Yosie Kristin Pandriyani; Hadiqotul Atfaliyah; Mulyadi, Rasad; Eva Sarifah Wardah (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
This study examines the book Uq?d al-Lujayn by Sheikh Muhammad Nawawi al-Bantani from the perspective of global Islamic philology and Islamic educational thought, focusing on the guidance on the rights and obligations of husbands and wives and its relevance to character education and Muslim family morals. This study uses a qualitative approach through library research, with the main data sources being the text of Uq?d al-Lujayn and supporting literature discussing family jurisprudence, Islamic character education, and maq??id al-syar?‘ah. The results of the study show that Uq?d al-Lujayn contains fundamental values such as justice, responsibility, compassion, deliberation, and education, which play an important role in shaping family character. Although written in the social context of the 19th century, the teachings in this book remain relevant when read critically and contextually with a hermeneutic and maq??id al-syar?‘ah approach. The conclusion of the study confirms that Uq?d al-Lujayn not only functions as a classic family fiqh text, but also as a source of ethics and pedagogy that is able to bridge the traditional Islamic scientific heritage with the needs of character education and morals of Indonesian Muslim families today.